The Kentucky Legislature : Two Decades of Change - Jewell, Malcolm E., 1928-2010 (Book collections on Project MUSE., 1988)
Twenty years ago the Kentucky General Assembly was one of the least powerful and least effective legislatures in the country, almost entirely dominated by the governor. Over the past two decades the legislature has changed -- gradually and with little public attention -- into a far more powerful, professional, and independent body. This book is a study of that process of change: its causes, the obstacles encountered, and the political and policy consequences. It is a study of changing relationships between governor and legislature, caused in part by less aggressive gubernatorial leadership and.